2016
DOI: 10.1097/meg.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

Model for end-stage liver disease score in the first 3 weeks after liver transplantation as a predictor for long-term outcome

Abstract: In conclusion, early postoperative MELD scores predict outcome after LTX. The postoperative MELD score at POD14 is a good predictor for patient survival and at POD7 for the graft survival after LTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Compared with the original study (12), the preoperative MELD score (21.9 vs. 12), WIT (43.9 vs. 7 min), CIT (492 vs. 424 min) and DRI (1.69 vs. 1.64) indicates that the donor, recipient and operation factors might contribute to the decrease cutoff value of MELDPOD5 (18.9 vs. 18.2) in our study cohort. On the contrary, Khandoga et al (15) in Germany proves that MELDPOD7 >29 had an excellent predictive power of 1-year graft survival, with the preoperative MELD score equal to 24.6 and CIT equal to 564 min. Therefore, the cutoff of 18.2 for MELDPOD5 might be more suitable for the Chinese population.…”
Section: Discussionmentioning
confidence: 90%
“…Compared with the original study (12), the preoperative MELD score (21.9 vs. 12), WIT (43.9 vs. 7 min), CIT (492 vs. 424 min) and DRI (1.69 vs. 1.64) indicates that the donor, recipient and operation factors might contribute to the decrease cutoff value of MELDPOD5 (18.9 vs. 18.2) in our study cohort. On the contrary, Khandoga et al (15) in Germany proves that MELDPOD7 >29 had an excellent predictive power of 1-year graft survival, with the preoperative MELD score equal to 24.6 and CIT equal to 564 min. Therefore, the cutoff of 18.2 for MELDPOD5 might be more suitable for the Chinese population.…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, another study done by Toshima et al [22] showed that the MELD score on POD2 with an optimal cutoff point of 19 was able to predict mortality and graft loss. Recently, Khandoga et al [23] reported that MELD on POD7 could reliably predict 1-year survival following LT (AUROC c-statistics: 0.73). The findings presented in our study generally support these data, and the predictive power of MELD score on POD5 (AUC: 0.712) could differentiate between survivors and non-survivors within 1 year post LT.…”
Section: Discussionmentioning
confidence: 99%
“…O escore MELD é amplamente utilizado para predizer o risco de morte de pacientes portadores de doença hepática terminal em um período de três meses, e busca reduzir a mortalidade entre pacientes na fila de espera por transplantes direcionando a alocação dos enxertos (99)(100)(101) . Além disso, investigação recente aponta outra aplicação: predição de uso de unidades de concentrados de hemácias no transoperatório em virtude de sua correlação positiva com o escore MELD (102) .…”
Section: Características Relacionadas àS Infecções Do Sítio Cirúrgicounclassified